2020
DOI: 10.1016/j.cjco.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Are Active Video Games Effective at Eliciting Moderate-Intensity Physical Activity in Children, and Do They Enjoy Playing Them?

Abstract: Background Despite current physical activity (PA) guidelines, children spend an average of 1-3 hours/day playing video games. Some video games offer physically active components as part of gameplay. We sought to determine if these active video games (AVGs) can elicit at least moderate PA in children, identify game elements important for PA, and determine if they are fun to play. Methods Twenty children aged 8 to 16 years underwent cardiopulmonary exercise testing to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Research has been conducted to assess the intensity of PA of various AVGs in the context of health recommendations for PA. Research results vary depending on the type of game and console. Some authors indicated that the intensity of PA is rather low [11], while others found that its levels are moderate or high [12][13][14][15]. There are reports that AVGs can be useful in combating overweight and obesity as they help increase daily dose PA and that playing these games can reduce BMI in children [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Research has been conducted to assess the intensity of PA of various AVGs in the context of health recommendations for PA. Research results vary depending on the type of game and console. Some authors indicated that the intensity of PA is rather low [11], while others found that its levels are moderate or high [12][13][14][15]. There are reports that AVGs can be useful in combating overweight and obesity as they help increase daily dose PA and that playing these games can reduce BMI in children [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Once again, the need for socialization and cooperative learning among all members is confirmed [ 27 ]. Thus, identifying what makes an app fun and engaging is important for an optimal game design [ 28 ]. It is important to focus on more user-identifiable characters, such as high-level realistic graphics and well-defined instructions; this has been suggested by a recent systematic review as one of the most important points for a successful healthy-lifestyle promotion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…ST refers to the use or viewing of anything with a screen with various types of ST requiring different levels of cognitive and physical engagement from the user (Norozi et al, 2020; Sweetser et al, 2012). Sanders et al have categorized four types of ST in Australian children: ‘educational ST (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, ST has the potential to foster increased and decreased participation in meaningful activities. While higher ST use has been linked to lower physical activity participation, which in turn affects HRQoL, video games that incorporate physical movement as part of gameplay can elicit moderate and vigorous-intensity physical activity, and are viewed by users as enjoyable (Norozi et al, 2020; Stiglic and Viner, 2019; Zhang et al, 2017). Furthermore, studies suggest that when adjusted for sociodemographic variables, ST’s correlation to displaced recreational activity participation in children no longer exists (Lees et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%